Primordial germ cell–like cells derived from canine adipose mesenchymal stem cells - Wei, Yudong (Cell Prolif, 2016)
OBJECTIVES: Previous studies have shown that adipose mesenchymal stem cells (AMSCs) share the potency of typical bone marrow mesenchymal stem cells (MSCs); however, there is little information concerning characteristics of canine AMSCs (CAMSCs); it has not previously been made clear whether CAMSCs would be able to differentiate into other cell types. MATERIALS AND METHODS: In this study, typical AMSC lines were established, and their characteristics including morphology, typical markers and differentiation potentiality were tested. RESULTS: The cells exhibited typical MSC morphology and were positive for CD90, CD44 and CD166, considered to be MSCs surface markers. They were negative for CD34 and CD45. The CAMSCs also exhibited embryonic stem cell (ESC) markers, including Oct4 and Sox2, at passage 2. In an appropriate microenvironment, CAMSCs differentiated into EBs and were able to produce cells of the three germ layers. These results indicate that established cells were putative adipocyte‐derived MSCs, which also displayed properties of ESCs. Moreover, when the CAMSCs were induced by bone morphogenetic protein 4 (BMP4), they differentiated into PGC‐like cells (PGCLCs) and male germ‐like cells, which were positive for PR domain‐containing 1 (Prdm1), PR domain‐containing 14 (Prdm14), doublesex and mab‐3 related transcription factor (Dmrt1), as well as for promyelocytic leukaemia zinc finger (Plzf). Quantitative real‐time PCR (qRT‐PCR) and western blotting analysis verified higher expression levels of these markers. CONCLUSION: This study provides an efficient approach to study germ cell development using CAMSCs.